Environmental Impact of Domestic Solar Water Heating Systems - Kalogirou, Soteris A. (My University, 2005)
In this paper a study on the environmental protection offered by domestic solar water heating systems is presented. The systems investigated employ electricity or diesel as back-up auxiliary energy. Both systems investigated produce about 2050 kWh of energy per year, cover about 89% of the hot water needs and give positive and very promising financial characteristics. The results show that by using solar energy for domestic water heating considerable amounts of greenhouse polluting gasses are avoided. The savings, compared to a conventional system, are about 80%, with electricity or diesel backup. With respect to life cycle assessment of the systems, the energy spent for the manufacture and installation of the solar systems is recouped in about 1.2 years, whereas the payback time with respect to emissions produced from the embodied energy required for the manufacture and installation of the systems varies from a few months to 3.7 years according to the fuel and the particular pollutant considered. Moreover the cost of damage avoided by some of the pollutants is investigated with respect to damages to crops, materials, mortality and morbidity. It was found that C£31 (Euro 51.7) are avoided per year when the system is using electricity as auxiliary and C£13 (Euro 21.7) when diesel is used. It can therefore be concluded that solar energy systems offer significant protection to the environment and cost savings and should be employed whenever possible in order to achieve a sustainable future.
Keywords: Environmental protection; Solar water heating systems